Third Five Year Plan Punjab State Annual Plan 1964-65 - Planning Commission (Planning Commission, 1964)
The annual Plan 1964-65 has been formulated keeping in view, on the one hand, the lessons of the mid-term appraisal undertaken recently and, on the other, the two-year perspective for 1964—66. the size of the Plan has been fixed at Rs 55.45 crores, which forms 24% of the total five-year outlay of Rs 231.39 crores.
Planning Department Punjab